Antibiotic treatment duration in diverticulitis, complicated urinary tract infection, and endocarditis: a retrospective, single-center study. (November 2022) - Frei, Nicolas Eduard; Dräger, Sarah; Weisser, Maja; Osthoff, Michael
Highlights: Antibiotic treatment duration was assessed in diverticulitis, urinary tract infection, and endocarditis. The treatment duration in diverticulitis and urinary tract infections exceeded recommendations in >50%. Longer treatment duration was associated with a lack of pathogen identification. Postdischarge treatment contributed significantly to the prolonged duration. Substantial opportunities exist to improve antibiotic prescribing in Switzerland. Abstract: Objectives: Despite the availability of international guidelines advocating shorter treatment durations, nonadherence to them is common. We assessed duration of antibiotic treatment for diverticulitis, complicated urinary tract infection (UTI), and endocarditis. Methods: Medical records of patients hospitalized with the previously stated diseases in 2017 and 2018 were randomly selected at a Swiss tertiary care hospital. The appropriateness of antibiotic treatment duration was assessed according to international and local guidelines. Results: A total of 243 patients were included in the study: 100 with diverticulitis, 200 with complicated UTI, and 43 with endocarditis. The dherence to local and international guidelines was 11% and 18% in diverticulitis, 39% and 40% in complicated UTI, and 84% and 86% in endocarditis, respectively. Nonadherence was primarily due to the prolonged treatment in diverticulitis and complicated UTI with a median duration of antibiotic treatment of 11 days (interquartile range 10-13) and 14 days (interquartile range 10-15), respectively. When pooling diverticulitis and complicated UTI cases, the identification of a pathogen in any microbiological sample was associated with an improved adherence to local guidelines in addition to hospitalization in a medical ward and infectious diseases consultation. Conclusion: Prolonged courses of antibiotic treatment were common and the treatment adherence to guidelines were poor in diverticulitis, moderate in complicated UTI, and excellent in endocarditis.